Mrs. Sargent (Lucille) Wright and booklets - Unknown:::Creator::::::::::::
Mrs. Sargent (Lucille) Wright handing booklets to Mrs. Fred May (middle) and another woman. There are several booklets of various topics on the table in the foreground.